The Cooperation of Two Manipulators with Fractional Controllers - Ferreira, N. M. Fonseca (2006)
This paper analyzes the dynamics and the implementation of fractional-order algorithms in the position/force control of two robots holding an object. The experiments reveal that fractional algorithms lead to performances superior to classical integer-order controllers.